Floristic Inventory and Distribution of Trees Along Urban National Streets and Roads in Cebu City, Philippines - Jumonong, Kristine Mae L.; Barliso, Angela C.; Lempio, Mariejayn C.; Ricaborda, Henry Clint D.; Garces, Jake Joshua C.; Picardal, Jay P. (Silliman Journal, 2022)
In urban landscapes, understanding the diversity of roadside vegetation is essential for better planning and designing of sustainable cities. The city of Cebu, located in central Visayas Philippines, is considered an urban tree biodiversity hotspot due to threats from continuous infrastructure development, road widening, and anthropogenic activities. To provide an update on tree diversity, as well as to determine the ecological status of the remaining trees thriving in Cebu City’s urban corridors, a floristic inventory and tree distribution survey (i.e. five national streets /roads) were conducted. Following a standard protocol for urban tree inventory, a tree distribution map was created using GIS, and information on urban corridors’ name, BDH of each tree, wire conflict, and tree condition were provided. Data showed 2,203 trees (45 genera and 27 families) were listed from these roadsides, with the proportion of alien trees higher (84.75%) than native trees (15.25%). Among these trees, 12.94% were in excellent tree condition, with narra (Pterocarpus indicus) and Manila palm (Adonidia merrillii) as the most abundant native tree, and mahogany (S. macrophylla) as the most exotic species. The distribution of trees by DBH classes along the five national roads showed that most trees belonged to the range of ≥ 70 cm, suggesting that mature trees dominated five urban corridors. In terms of tree protection and management, most trees in Cebu City were recommended for silvicultural treatment to salvage mother trees from further damage. Baseline data gathered in this study may serve as guide for urban planners for a responsible and sustainable urban tree conservation and management.